Potential of fern species to forecast microclimate changes at urban area - Mohd Latif, Nur Hanie; Md. Jais, Mohd. Arami; Tukiman, Izawati; Othman, Rashidi (UKM, 2011)
The aim of the research is to explore the potential of fern species in landscape ecology, as natural indicators to forecast the microclimate changes in the urban area and at the same time can be applied in landscape design. Ferns which also called as pteridophyte are not only valuable in term of its ethno-botany uses such as food and medicine but also useful in ecological values. For example, fern can be used to treat unhealthy environment such as absorbing the methane gas, fertilizing the land and to treat heavy metal such as arsenic. Fern also can be used as an ecological indicator for micro climate changes. Fern species are able to indicate similar relationships between the environment and also as indicators for the early signs of climate changes at different latitude. In this study, two set of case studies were made and observed. The observation of different changes of latitude were done at Gunung Jerai and Lata Jarum while the urban heat island (UHI) study were conduct at rooftop garden of Hospital Serdang and Secret Garden, One Utama Shopping Complex (OU). From the observation made at Gunung Jerai and Lata Jarum, there were 12 fern species detected at Gunung Jerai while 20 fern species at Lata Jarum. The species found at Gunung Jerai were Selaginella willdenowii, Arcypteris irregularis (0 to 100 meter elevation), Adiantum caudatum, Pityrogramma calomelanos (101 to 200 meter elevation), Histiopteris stipulacea, Athyrium cordifolium, Osmund wachellii (201 to 300 meter elevation), Histiopteris stipulacea, Cyathea contaminans (301 to 400 meter elevation), Histiopteris stipulacea and Lygodium circinnatum (401 to 500 meter elevation), while Selaginella willdenowii, Asplenium nidus., Arcypteris irregularis, Cyathea contaminans, Dicranopteris linearis (201 to 300 meter elevation), Phymatodes scolopendria, Antrophyum callifolium, Arcypteris irregularis, Phymatodes crustacea, Selaginella willdenowii, Angiopteris evecta, Aglaomorpha heraclea (301 to 400 meter elevation), Osmunda wachellii, Adiantum latifolium, Arcypteris irregularis, Angiopteris evecta, Athyrium cordifolium, Selaginella plana, Tectaria semipinnata, and Cyathea contaminans (401 to 500 meter elevation), were found at Lata Jarum. Therefore, climate is the main factors of affecting the occurrences of the fern species. The microclimate has strong relationship with the distribution of the fern species whereas altitude influenced the distribution of fern species. Therefore fern species are excellent phytoindicator which can be used as indicator for unhealthy environment such as harsh urban area environment.